Modern weapons and military equipment for issue 4/2014 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
RUSSIAN ARMED MOBILE ROBOTICS AND AUTOMATION Russia develops models of robotic platforms for carrying weapons, equipment, mine detection and clearance, fire equipment and observation-scout day-night optoelectronicdevices. Used and the experience of modern wars, as in the example of the Libyanarmed pickup truck served to develop the idea of robotic rocket launchers. With roboticvehicles suggested the idea of robotic mobile station control robotic vehicles on the battlefield. Experiment and the robotic platform - amphibians. Parallel to the progess of other armies of the world in the development and application of armed robotic platform. In conclusion to this approach, the development of automation and robotics Russian military experts tend to be up with the developed world, and even to take precedence on the basis of experience and knowledge. Besides trying to be completely equal footing with other world powers when it comes to utomatizovano battlefield and precisionwarfare.